The Financial Performance and Financial Leverage of Retail Listed Firms in South Africa: Array - Mamaro, Lenny Phulong; Legotlo, Tsholofelo Gladys (Acta Universitatis Danubius. Œconomica, 2021)
The study investigates the relationship between financial performance and dividend payout of Retail firms over eleven years from 2010 to 2020. The rationale behind this call is that a lot of research on the relationship between financial leverage and dividend payout originate from developed countries. It is on this background that this study tries to investigate the relationship between firm growth and dividend payout from a South African perspective. The quantitative research design was employed to investigate the influence of financial performance on financial leverage of Listed Retail firms using panel data analyses. Secondary data collection consists of annual financial reports of Retail firms for a period from 2010 to 2020 which consist of 170 observations. The empirical results show that financial performance is positively associated with a financial leverage of listed Retail firms, while other variables (financial leverage, firm growth) positively significant influence financial performance. Liquidity is positively but insignificantly influence financial performance while firm size is negatively insignificantly affect financial performance. The study is limited to the Retail sector only which means cannot generalise the overall findings to other sectors of the economy. These results might benefit researchers, managers and investors and provide a guideline to the relevant literature. . In South Africa, there is an insufficient amount of evidence on the relationship between financial leverage and financial performance. In South Africa, as a developing country, there is a need for more comparable studies investigating this phenomenon.